Narrative (sub)Versions: How Queer Palestinian Womyn 'Queer' Palestinian Identity - Moussa, Ghaida (Université d'Ottawa / University of Ottawa, 2011)
In asking ‘How do queer Palestinian womyn ‘queer’ Palestinian identity”, the present research focuses on the various forms of traditional, narrative, and creative resistance practices of Palestinian womyn who challenge the following three narratives: 1) the national narrative which tags ‘queer’ as ‘Other’ and which posits the national movement at the top of the hierarchy of struggles; 2) the colonial narrative which is sustained by the Israeli public relations campaigns aiming to portray Israel as a modern, progressive, safe gay haven for queers, in opposition to a Palestine and Arab World which are said to be integrally homophobic, barbaric, regressive, etc. in an attempt to ‘pinkwash’ the occupation; and 3) the neocolonial narrative in which Western and Israeli Jewish queer movements reproduce colonial dynamics in their attempt to ‘save’ Palestinian queers who are deemed to be powerless, voiceless victims in need of saving.
Keywords: Palestine; queer; social movements; resistance; postcolonial; transnational; solidarity; feminist methodology; identity